(untitled) (International Journal of Mathematics and Physics, 2018)
The work is devoted to Mössbauer studies of new building materials derived from wastes from coal-fired power plants. Measurements of Mössbauer spectrometers were carried out on the MC1104EM unit in the regime of constant acceleration with a source of 57Co (Cr). The elemental composition of each sample was determined by means of X-ray fluorescence analysis (XRF) on the RLP-21 installation. According to the results of studies of volume-surface concentric-zonal color effects in zoloceramic materials, the phase composition of iron compounds and their ratios is established by the Mössbauer method, and their elemental composition with 32 components is determined with high accuracy by means of XRF. The technology of obtaining gold-ceramic materials with volumetric-surface color effects is described.